"I Just Like to Share My Life with My Partner:" Mobile Phone Integration in Romantic Partners' Face-to-Face Interactions. Issue 4 (8th August 2022) - Kelly, Lynne; Miller-Ott, Aimee E.
ABSTRACT: Participants ( N = 312) in romantic relationships completed an online survey to determine common integrated phone activities, motivations for integrating phones into time together, and whether phone integration is associated with relationship satisfaction. The most frequent activities included showing social media posts, photos, and videos; showing texts; and involving the partner in video calls. Primary motivations for integrating phones into partners' co-present time were enjoyment, psychological inclusion, phubbing avoidance, transparency, and habitual use. Findings indicate that participants were often intentional in integrating the phone into co-present time, and frequency of joint involvement with the phone was associated with relationship satisfaction.